Black College Athletes’ Perceptions of Academic Success and the Role of Social Support - Carter-Francique, Akilah; Hart, Algerian; Steward, Astin (Journal of Intercollegiate Sport, 2013)
The purpose of this study is to understand Black college athletes’ perceptions of academic success and how social support contributes to their academic success at predominantly white institution of higher education (PWIHE). Utilizing a qualitative approach, the authors conducted narrative interviews to capture the experiences of Black college athletes (n = 9) at a PWIHE in the southwest region of the United States. Critical race theory was employed to understand the social realities and academic experiences of racial minorities within the academic environment. Findings revealed Black college athletes’ social support was based on their role as a college athlete and as a racial minority, thus reinforcing the notion of social isolation and alienation. Acknowledging the National Collegiate Athletic Association’s (NCAA) definition of academic success (e.g., grade point average, graduation), it is plausible that understanding how college athletes perceive academic success and value of social support can aid in achieving academic success according to the NCAA of not only Black college athletes, but a diverse body of college athletes.